2013
DOI: 10.1016/j.jcm.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and Traditional Chinese Medicine for the management of a 35-year-old man with chronic prostatitis with chronic pelvic pain syndrome

Abstract: Objective: The purpose of this case report is to describe the resolution of pain in a patient with chronic prostatitis and chronic pelvic pain syndrome after receiving a course of management using acupuncture and Chinese herbal medicine. Clinical features: A 35-year-old man presented with chronic prostatitis with chronic pelvic pain syndrome. He scored 38 out of a possible 43 on the National Institutes of Health/Chronic Prostatitis Symptom Index (NIH/CPSI) that rates pain, urinary symptoms, and quality of life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…[24] TCM therapy mainly achieves therapeutic effects by stimulating the body's righteousness and regulating the balance of qi and blood. [25] In recent years, TCM therapy has been widely used in clinical trials of CP/CPPS. Recent studies have shown that TCM can alleviate the pain caused by CP/CPPS to a certain extent and improve the quality of lives of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] TCM therapy mainly achieves therapeutic effects by stimulating the body's righteousness and regulating the balance of qi and blood. [25] In recent years, TCM therapy has been widely used in clinical trials of CP/CPPS. Recent studies have shown that TCM can alleviate the pain caused by CP/CPPS to a certain extent and improve the quality of lives of patients.…”
Section: Discussionmentioning
confidence: 99%
“…TCM believes that the cause of CP/CPPS is mainly in the kidney. [13,14] Yin deficiency and heat, qi stagnation and blood stasis is its main pathogenic factor. Through the application of traditional Chinese medicine in the treatment of CP/CPPS's unique diagnosis and treatment system, clinical efficacy is significant.…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture therapy mainly achieves therapeutic effects by stimulating the body's righteousness and regulating the balance of qi and blood. [25] In recent years, acupuncture therapy has been widely used in clinical trials of CP/CPPS. Recent studies have shown that acupuncture can alleviate the pain caused by CP/CPPS to a certain extent and improve the quality of lives of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] TCM mainly achieves therapeutic effects by stimulating the body's vital qi and regulating the balance of qi and blood. [ 22 ] Modern studies have shown that the effective active ingredients in TCM can achieve the therapeutic purpose by improving the blood supply of peripheral blood vessels. [ 19 , 20 ] Moreover, Chinese medicine can relieve the pain and improve the quality of life of patients with CP/CPPS, and these effects are persistent.…”
Section: Introductionmentioning
confidence: 99%